Faith-Integrated Environmental Education in a Muslim-Majority Rural Community: A Qualitative Case Study South Sulawesi, Indonesia - Rudhi Rudhi; Herianti Herianti; Nurdin Nurdin; Nursyamsidar Nursyamsidar; Nurhaliza Nurhaliza; Nia Kartika Putri; Sita Damayantih; Indo Aco; Rahman Rahman; Naufal Fajrul Ihsan; Agung Setia Budi Wahid (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Education for Sustainable Development increasingly recognizes that durable environmental behavior is rooted in intrinsic motivation rather than information provision alone. In Muslim-majority communities, Islamic ecotheology offers a culturally authentic foundation for environmental education, yet empirical research on its operationalization in real community settings remains limited. This qualitative case study investigates how Islamic ecotheological values function as a framework for non-formal and informal environmental education in Ganra Village, South Sulawesi, Indonesia, examining the factors sustaining community-wide environmental learning. Data were collected through purposive semi-structured interviews, participatory observation, and document analysis, then analyzed using the Miles, Huberman, and Saldaña interactive model. Three principal findings emerged: first, environmental awareness is grounded in Islamic faith, framing environmental care as ibadah (worship) through khalifah (vicegerency) and mizan (balance); second, ecotheological values are operationalized through five structured educational channels, including communal rituals and the BERGEGAS waste management program; third, six interdependent factors sustain learning, notably strong leadership, village regulations, and a deep Islamic heritage. The Ganra Village case demonstrates that faith-integrated environmental education, when institutionally scaffolded, produces highly persistent pro-environmental outcomes. This ProKlim-awarded model offers a replicable template for faith-based environmental education globally, advancing scholarship by demonstrating how ecotheology functions as a pedagogically coherent framework.